Major Cereal Crops Damage by Wildlife: A Case Study from Chitwan National Park, Nepal - Ghimire, Sunita; Devkota, Durga; Dhakal, Shiva Chandra; Upreti, Bishnu Raj (Agriculture Development Journal, 2022)
Human-wildlife conflict is a major issue for policymakers and conservationists due to economic damage by wild animals, resulting in increasing poverty. This study assesses the wildlife-induced damage to the major food crops viz. rice, wheat, and maize. A total of 434 households from the 10 forest user groups near the Chitwan national parks and buffer zone were randomly selected and interviewed by the use of questionnaires in 2021. A total of 87.86% of rice-growing households reported damage to rice, whereas 90.32% and 87.68% of households reported damage to wheat and maize, respectively. The annual loss of 78 kg of rice per household (NRs. 1776 at prevailing market rates) was reported in the study area. The loss of wheat and maize per household was 86 and 96 kg with the worth of NRs. 2523 and 2019, respectively. The severity of wildlife-induced damage to crops was more near the borders of national parks and buffer zone. Apart from the construction and maintaining permanent fences on the border of the national parks, there should be the provision of conservation education to communities residing along the buffer zone and near the protected areas to practice sustainable agriculture and income-generating programs that are conservation-friendly.